Age- and sex-specific excess mortality associated with influenza in Shanghai, China, 2010–2015. (September 2020) - Jin, Shan; Li, Jing; Cai, Renzhi; Wang, Xiling; Gu, Zhen; Yu, Huiting; Fang, Bo; Chen, Lei; Wang, Chunfang
Highlights: The mortality burden of influenza has been substantial in Shanghai, especially among the elderly. Excessive mortality associated with influenza B virus is dominated by B(Yamagata) lineage. The evidence for sex differences in influenza-associated mortality for respiratory and circulatory diseases is limited. Abstract: Objective: Few studies have explored the different lineages of influenza B viruses, which cause excessive fatalities. This study aimed to estimate age- and sex-specific excessive mortality associated with influenza subtypes/lineages in Shanghai, during 2010–2015. Methods: We used quasi-Poisson regression models to fit weekly numbers of deaths from various causes by adjusting long-term trend, seasonal trend, and absolute humidity as confounding factors. The mortality burden associated with influenza subtypes/lineages was estimated by age and sex. Results: The average influenza-associated excessive mortality rate in deaths coded as all-cause was 27.66 (95%CI: 22.30–33.88) per 100, 000 person-years. The excessive deaths from six underlying causes in people aged ≥65 years weight heavily. Compared to influenza B(Victoria) lineage, influenza B(Yamagata) lineage had more effect on the influenza-associated disease burden, particularly in patients with respiratory and circulatory diseases. There was no statistical significance of sex in the mortality burden associated with influenza. Conclusion: Disproportionate mortality associated with influenza B virus is dominated by B(Yamagata) lineage in Shanghai, and the evidence for sex differences in the influenza-associated mortality burden for respiratory and circulatory diseases is limited. Improving the vaccination of the elderly and strengthening laboratory-based surveillance of influenza B lineages in Shanghai are needed to reduce this influenza's disease burden.